Interview with John W. Meyer: If You Study Organizations You Should Not Believe in Them (interviewed by Elena Gudova) - John W. Meyer (Экономическая социология, 2020)
An interview with John W. Meyer, emeritus Professor of Sociology, and by courtesy Education, at Stanford University, was conducted in October 2019 during his visit to the 10th International Russian Higher Education Conference (RHEC) in Moscow on “Contributions of Higher Education to Society and Economy: Global, National and Local Perspectives.” The interview was performed by Elena Gudova, PhD and a lecturer in the Department of Economic Sociology at the Higher School of Economics. John Meyer talks about the rise of hyper-managerialism and its implications for modern organizations. While previously, organizations tended to be subordination actors, today they have more legitimation in choosing mission and purposes, which marks a shift from management authority toward leadership and implies a need for managers with charismatic qualities. Business schools, in their courses and educational processes, emphasize the importance of failures as part of entrepreneurs’ experiences, while questions of vision are rarely a part of the agenda. Still, even a great charismatic leader/entrepreneur may lack authority because of a decontextualized vision as local communities’ interests are usually not represented. Organizations with good vision (i.e., with proper corporate social responsibilities) may legitimate themselves through the routinization of the leader’s charisma, the incorporation of norms of good citizenship, and the self-management of employees and citizens. As Meyer puts it, “You have to be an okay-person in the modern hyper-organizational context.” Due to these new scripts in the character of an individual, John Meyer discusses distinctions between the American and German educational systems and some possible outcomes for the world based on the German educational model instead of on the American one. As current types of organizational responses might be treated as invasive for individuals (even though they are useful in many ways), the German system resists many of the hyper-liberal changes in a much better way. Another focus of Meyer’s interests is connected with changes in universities and those in science in general. He talks about the mutual influence of society and academia and the legitimation of scientific knowledge, both per se and in educational process. A simple, but still important, issue regards keeping a research distance and asking the right questions, as moral commitment might weaken the research. The solution may be in comparing education to the forces that produce the observed changes, and not to what we imagine to be an ideal educational process and product.